Improving reading comprehension skills using Know-Want-Learn (KWL) strategy in grade V of SDN 196/II Taman Agung, Bungo Regency - Ulya Desmawati; Reni Guswita (Inovasi Kurikulum, 2025)
Indonesian language systematically from elementary to higher education has an important meaning not only in strengthening national identity, but also in encouraging the effectiveness of communication and supporting national development. This study aimed to enhance the reading comprehension skills of fifth-grade students at SDN 196/II Taman Agung, Bungo Regency, where initial observations indicated low performance. The research employed a Classroom Action Research (CAR) methodology conducted over two cycles, following the Kemmis and McTaggart model, which includes planning, acting, observing, and reflecting stages. The subjects were 15 fifth-grade students during the second semester of the 2024/2025 academic year. Data collection instruments consisted of observation sheets for teacher and student activities, reading comprehension tests, and documentation. The findings revealed significant improvements across each cycle. Teacher activity improved from the "High" category in cycle Ito "Very High" in cycle II. Student engagement also increased from "Fairly High" in cycle I to "High" in cycle II. The most notable enhancement was in student learning outcomes, with the percentage of students achieving reading comprehension mastery rising, surpassing the established performance indicator Therefore, it is concluded that the implementation of the Know, Want to Know, and Learned (KWL) strategy is effective in improving students' reading comprehension skills.   Abstrak Bahasa Indonesia secara sistematis sejak pendidikan dasar hingga pendidikan tinggi memiliki arti penting tidak hanya dalam memperkuat jati diri bangsa, tetapi juga dalam mendorong efektivitas komunikasi dan mendukung pembangunan nasional. Penelitian ini bertujuan untuk meningkatkan keterampilan membaca pemahaman peserta didik kelas V di SDN 196/II Taman Agung, Kabupaten Bungo, yang teridentifikasi masih rendah. Metode yang digunakan adalah Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus, mengacu pada model Kemmis dan McTaggart yang meliputi tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah 15 peserta didik kelas V pada semester genap tahun ajaran 2024/2025. Instrumen pengumpulan data mencakup lembar observasi aktivitas pendidik dan peserta didik, tes pemahaman membaca, serta dokumentasi. Hasil penelitian menunjukkan peningkatan signifikan pada setiap siklus. Aktivitas pendidik meningkat dari kategori "Tinggi" pada siklus I menjadi "Sangat Tinggi" pada siklus II. Keaktifan peserta didik juga naik dari "Cukup Tinggi" pada siklus I menjadi "Tinggi" pada siklus II. Peningkatan paling signifikan terlihat pada hasil belajar peserta didik, di mana persentase ketuntasan membaca pemahaman meningkat melampaui indikator kinerja yang ditetapkan. Dengan demikian, disimpulkan bahwa penerapan strategi Know, Want to Know, and Learned (KWL) terbukti efektif dalam meningkatkan keterampilan membaca pemahaman peserta didik. Kata Kunci: KWL; literasi; membaca; pemahaman membaca